Wie nationale Souveränität zu Markte getragen wird - Gerstenberger, Heide; Welke, Ulrich (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2005)
While free trade zones, offshore banking and open ship registers have long been known, it is only during the last three decades that the offshore complex has become an important structural element of the world market. Governments offer special conditions for non-citizens on a world market. While these “havens” are often made use of for criminal activities, their use has also become a feature of legal strategies in the global economy. As far as the shipping industry is concerned “flags of convenience” offer several possibilities for cost reduction, the most important factor being the possibility to legally circumvent national labor markets. Most seafarers of today therefore work in a politico-legal no-man’s land.